2011
DOI: 10.5251/ajsir.2011.2.6.877.882
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination in canned fish marketed in Ghana

Abstract: The concentrations of Pb, Zn, Fe, Cd, Mn and Hg in 46 canned fish samples of nine different brands purchased within Kumasi in the Ashanti Region of Ghana were determined using the Flame Atomic Absorption Spectrophotometer for Pb, Zn, Fe, Cd and Mn and direct mercury analyzer (DMA) for Hg. The ranges obtained for the elements analyzed in µg/g (wet weight) are as follows: Pb (0.058 -0.168), Zn (0.010 -0.370), Hg (0.088 -0.410), Mn (0.001 -0.057), Fe(0.990 -32.607) and Cd, below detection limit in all the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
3
21
3
Order By: Relevance
“…Most available data refers to tuna as this species of fish is particularly popular among consumers around the world (Boadi et al 2011), which was also supported by the present authors' own studies. The presented studies revealed that canned tuna contained 1.02-1.705 lg Cd and 1.19-7.89 lg Pb per 100 g. The content measured by other authors, based on research carried out in various countries (Ikem and Egeibor 2005;Boadi et al 2011) was similar to that determined by the present authors; however, some authors obtained lower results (Mahalakshmi et al 2012). In turn, results referring to the content of Cd and Pb in canned salmon and mackerel, available in literature (Ikem and Egeibor 2005), are lower compared to those obtained in these authors' own studies.…”
Section: Discussionsupporting
confidence: 89%
“…Most available data refers to tuna as this species of fish is particularly popular among consumers around the world (Boadi et al 2011), which was also supported by the present authors' own studies. The presented studies revealed that canned tuna contained 1.02-1.705 lg Cd and 1.19-7.89 lg Pb per 100 g. The content measured by other authors, based on research carried out in various countries (Ikem and Egeibor 2005;Boadi et al 2011) was similar to that determined by the present authors; however, some authors obtained lower results (Mahalakshmi et al 2012). In turn, results referring to the content of Cd and Pb in canned salmon and mackerel, available in literature (Ikem and Egeibor 2005), are lower compared to those obtained in these authors' own studies.…”
Section: Discussionsupporting
confidence: 89%
“…Liver and gills are metabolically active tissues and accumulate heavy metals of higher levels than muscles as it has been observed in this present study and in many experimental and field studies [41,42]. The levels of heavy metals in fish absorption through food depend upon many factors like the duration of exposure of fish to contaminants in the water, the feeding habits, water chemistry and any contamination of fish during handling and processing, and fish sex, weight, season [43].Those heavy metals accumulate in metabolic organs and stored are detoxificated by producing metallothioneins. In the present study results showed that metal accumulation was higher in gills and liver, whereas it was lower in muscles.…”
Section: Resultssupporting
confidence: 73%
“…The Hg concentrations in the muscle of mackerels were lower than the levels previously reported (jack mackerel, Orleans: 61 ng/g and jack jurel mackerel, Chicken of the Sea: 50 ng/g) by Shim et al (2004). Similarly, Hg concentrations in sardines were lower than the Hg levels in canned sardines (117 ng/g, 141 ng/g, and 143 ng/g) reported by Boadi et al (2011). The current study found that the percentage of MeHg in T-Hg in canned fish samples ranged from 90.4% to 100%, which was consistent with levels found in fish, squid and shrimp in previous studies (Bloom, 1992;Yoshimoto et al, 2016;Hoang et al, 2017).…”
Section: Discussioncontrasting
confidence: 46%
“…Canned seafood is a known source of MeHg exposure (Boadi et al, 2011;Siedlikowski et al, 2016), and canned tuna contains high concentrations of Hg (Alcala-Orozco et al, 2017). In all samples tested, only Hg concentrations in the muscle of yellowfin tuna exceeded the maximum level allowed by WHO, 500 ng/g for MeHg in all types of fish (United Nations Environment Programme, 2002), and permitted by Japanese regulations, 400 ng/g for T-Hg and 300 ng/g for MeHg (Notice Kannyu No.99, 1973).…”
Section: Discussionmentioning
confidence: 99%